Anodal transcranial direct current stimulation in chronic migraine and medication overuse headache: A pilot double-blind randomized sham-controlled trial. Issue 1 (January 2021) - De Icco, R.; Putortì, A.; De Paoli, I.; Ferrara, E.; Cremascoli, R.; Terzaghi, M.; Toscano, G.; Allena, M.; Martinelli, D.; Cosentino, G.; Grillo, V.; Colagiorgio, P.; et al.
Highlights: The study aims to assess the role tDCS as add-on to detoxification in chronic migraine associated to medication overuse headache. Anodal tDCS was superior to sham stimulation in reducing monthly migraine days after 1 month and 6 months from detoxification. Alpha rhythm was significantly enhanced over occipital leads in the tDCS group when compared to the sham group. Abstract: Objectives: Little evidence is available on the role of transcranial direct current stimulation (tDCS) in patients affected by chronic migraine (CM) and medication overuse headache (MOH). We aim to investigate the effects of tDCS in patients with CM and MOH as well as its role on brain activity. Methods: Twenty patients with CM and MOH were hospitalized for a 7-day detoxification treatment. Upon admission, patients were randomly assigned to anodal tDCS or sham stimulation delivered over the primary motor cortex contralateral to the prevalent migraine pain side every day for 5 days. Clinical data were recorded at baseline (T0), after 1 month (T2) and 6 months (T3). EEG recording was performed at T0, at the end of the tDCS/Sham treatment, and at T2. Results: At T2 and T3, we found a significant reduction in monthly migraine days (p = 0.001), which were more pronounced in the tDCS group when compared to the sham group (p = 0.016). At T2, we found a significant increase of alpha rhythm in occipital leads, which was significantly higher in tDCS group when compared to sham group. Conclusions: tDCS showed adjuvant effects to detoxification in the management of patients with CM and MOH. The EEG recording showed a significant potentiation of alpha rhythm, which may represent a correlate of the underlying changes in cortico-thalamic connections. Significance: This study suggests a possible role for tDCS in the treatment of CM and MOH. The observed clinical improvement is coupled with a potentiation of EEG alpha rhythm.